2020
DOI: 10.1016/j.energy.2019.116815
|View full text |Cite
|
Sign up to set email alerts
|

Gas production from methane hydrates upon thermal stimulation; an analytical study employing radial coordinates

Abstract: In this study, a radial analytical model for methane hydrate dissociation upon thermal stimulation in porous media considering the effect of wellbore structure has been developed. The analytical approach is based on a similarity solution employing a moving boundary separating the dissociated and undissociated zones. Two different heat sources are considered: i) line heat source; and ii) wellbore heat source with specific thickness consisting of casing, gravel, and cement. The temperature and pressure distribut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 74 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Thus, the highest production rate of methane gas was produced via the two methods combined together [43]. Roostaie and Leonenko [44] used thermal heating technique to dissociate methane hydrate. The results of the authors' study showed that thermal heating can be successfully applied in gas hydrate dissociation [44].…”
Section: Heatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the highest production rate of methane gas was produced via the two methods combined together [43]. Roostaie and Leonenko [44] used thermal heating technique to dissociate methane hydrate. The results of the authors' study showed that thermal heating can be successfully applied in gas hydrate dissociation [44].…”
Section: Heatingmentioning
confidence: 99%
“…Roostaie and Leonenko [44] used thermal heating technique to dissociate methane hydrate. The results of the authors' study showed that thermal heating can be successfully applied in gas hydrate dissociation [44].…”
Section: Heatingmentioning
confidence: 99%
“…Natural gas hydrate is typically distributed in marine sediments and permafrost regions and is expected to become a significant successor to natural gas. Therefore, realizing the commercial development of natural gas hydrate sediments possesses significance in ensuring a sustainable energy supply. Many countries, such as the United States, Japan, China, and so on, have successfully carried out trial production of natural gas hydrate deposits at the moment. However, the phenomena of low productivity, sanding, unsustainable production, and high development cost have been encountered during trial tests. , Due to the vast cost, it is impossible to figure out the production behavior of natural gas hydrate deposits in detail just through a pilot test by depressurization, thermal stimulation, inhibitor injection, CO 2 replacement and the joint development technology. It is an alternative approach to authentically reshape hydrate-bearing sediments and unravel the production characteristics through indoor experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al and Wang et al numerically examined the relationship between heat transfer and hydrate decomposition in a hydrate-bearing core sample and reached a conclusion that thermal stimulation dramatically promoted the hydrate decomposition reaction and gas recovery efficiency in a low-permeability deposit. Roostaie and Leonenko , developed an analytical approach of wellbore heating coupled with hot water circulation and investigated the NGH decomposition behaviors in the reservoir. Yadav et al and Wang et al both proposed a microwave heating technology for NGH exploitation and found that this technology could significantly improve gas recovery and achieve a high energy efficiency.…”
Section: Introductionmentioning
confidence: 99%